Label-free immunosensing by long period fiber gratings at the lowest order cladding mode and near turn around point. (October 2021) - Dey, Tanoy Kumar; Tombelli, Sara; Biswas, Palas; Giannetti, Ambra; Basumallick, Nandini; Baldini, Francesco; Bandyopadhyay, Somnath; Trono, Cosimo
Highlights: Fabrication of long period fiber gratings with lowest order cladding mode near turn around point. Maximum enhancement of the evanescent field of the sensor. Microfluidic thermostated flow-cell. Label free IgG/anti-IgG immunoassay performed in human serum. Limit of detection 0.16 ng/ml (1.06 pM). Information on the binding kinetics. Abstract: A long period fiber grating has been fabricated by combining two sensitivity enhancement techniques, the turn around point (TAP) and the maximum enhancement of the evanescent field by obtaining the lowest order cladding mode (LP0, 2 cladding mode). A label-free immunoglobulin G/anti immunoglobulin G (IgG/anti-IgG) immunoassay in serum has been performed with the sensor inside a thermostated closed flow cell. Real time kinetics of the IgG and anti-IgG binding has been monitored and evaluated. By measuring the dual peak resonance of the LP0, 2 cladding mode, a limit of detection of 0.16 ng/ml (1.06 pM) for anti-IgG has been achieved.